Ultrasonic measurement of BMD,FRAX~? and OSTA in the prediction of fracture risk in maintenance hemodialysis - ZHANG Yan-ni; XIA Meng-di; WANG Bao-fu; XIE Xi-sheng (Linchuang shenzangbing zazhi)
Objective To evaluate the and compare the validity of quantitative ultrasound bone(QUS)(BMD),FRAX Methods measurements to measure bone mineral density and OSTA for predicting(MHD)fracture risk in maintenance hemodialysis patients.from 113 patients from the Blood Purification this Center The of Nanchong Central Hospital January factors were 2013 to January 2015 were data fitted of in information,clinical about osteoporosis,and study.one demographic risk of the BMD from in third of distal was radius the MHD FRAX patients and collected.ROC The probability of fracture risk MHD patients calculated by OSTA.curves patients females were was drawn.The validity of BMD,FRAX and fitted OSTA in for predicting fracture risk There in MHD were compared.50 Results with 113patients were years predicting 56 fracture risk.63 and males age ranging(years)()patients,and13 the-83 mean 6±16.0 87 The fracture The group had 14 12.39%..()control group had 99.61%patients.±1.91 average BMD in the fracture The group and control()group was-3.69±2.32 and-2.09 respectively P<0.05 FRAX~?index showed.(z=-4.837,P<0.01).The average score in the significant fracture difference between the two was groups-3.69(<0.05).group and ROC control group±2.76 and 0.46±3.60 respectively 95%P of BMD,FRAX~?and OSTA();AUC areas of curves.816 were 0.688 CI 0.534-0.842();(),respectively.0.900 values 95%CI 0-0.984 0.868 95%CI 0.793-0.942 The cutoff of BMD,FRAX~?and OSTA-2.45,3.25 and-2.93 respectively.Conclusions were of BMD,FRAX~?and OSTA may discriminate fracture risk among MHD higher All the patients and FRAX~?had validity.